The Influence of Digital Technology Utilization on Employee Performance through Work Motivation as a Mediating Variable - Bahri, Hairul; Juliana, Ahmad; Azwar, Muhammad (Jurnal Mirai Management, 2025)
Digital transformation in the public sector demands effective technology utilization and human resource readiness. This study investigates the effect of digital technology utilization on the performance of Government Employees with Work Agreements (P3K), with work motivation as a mediating variable. A quantitative approach was employed, using a structured questionnaire distributed to 91 P3K employees in Bulungan Regency, North Kalimantan. Multiple linear regression and mediation analysis were conducted to examine variable relationships. The findings indicate that digital technology utilization has a positive and significant effect on P3K performance (β = 0.068; p < 0.001). Work motivation also significantly affects performance (β = 0.074; p < 0.001) and mediates the relationship between technology and performance (β = 0.002; p < 0.001). The results suggest that while digital tools enhance work efficiency, their impact is optimized when employees are highly motivated. Thus, work motivation serves as a crucial factor in the successful implementation of technology. The influence of digital technology on performance is both direct and mediated by work motivation. Digital transformation policies must incorporate motivational strategies to achieve optimal employee performance. Keywords: Digital technology, Work Motivation, Performance, P3K, Mediation